2014
DOI: 10.1212/wnl.0000000000000592
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity in the basal ganglia network differentiates PD patients from controls

Abstract: Objective: To examine functional connectivity within the basal ganglia network (BGN) in a group of cognitively normal patients with early Parkinson disease (PD) on and off medication compared to age-and sex-matched healthy controls (HC), and to validate the findings in a separate cohort of participants with PD.Methods: Participants were scanned with resting-state fMRI (RS-fMRI) at 3T field strength.Resting-state networks were isolated using independent component analysis. A BGN template was derived from 80 eld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
163
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(184 citation statements)
references
References 42 publications
17
163
4
Order By: Relevance
“…Our study uses an unbiased, data-driven approach based on ICA that can emphasize broader changes in functional connectivity not restricted to a set of predefined seeds. Other important studies employing ICA [8,15,22,23] have been already published. The advantage of our analysis approach is that it evaluates connectivity changes in all neural networks not just in a preselected few (1 to maximum 5 networks) [8,15,22,23].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our study uses an unbiased, data-driven approach based on ICA that can emphasize broader changes in functional connectivity not restricted to a set of predefined seeds. Other important studies employing ICA [8,15,22,23] have been already published. The advantage of our analysis approach is that it evaluates connectivity changes in all neural networks not just in a preselected few (1 to maximum 5 networks) [8,15,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies experimented with different ICA dimensionalities and found that 50 is the minimum number of components necessary to separate known networks, in particular for separating the basal ganglia network from the sensorimotor and salience networks [23]. Another study suggested a minimum of 60 components in order to detect motor, language, and working memory networks [56].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations